2004
DOI: 10.1038/nature02413
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for the existence of iron-rich metal in the Earth's lower mantle

Abstract: The oxidation state recorded by rocks from the Earth's upper mantle can be calculated from measurements of the distribution of Fe3+ and Fe2+ between the constituent minerals. The capacity for minerals to incorporate Fe3+ may also be a significant factor controlling the oxidation state of the mantle, and high-pressure experimental measurements of this property might provide important insights into the redox state of the more inaccessible deeper mantle. Here we show experimentally that the Fe3+ content of alumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
366
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 536 publications
(413 citation statements)
references
References 27 publications
21
366
0
2
Order By: Relevance
“…Given the totality of these observations, we suggest that the resolution of conflicting fO 2 indicators is that in the deep mantle (Ͼ300 km) the fO 2 is low and the elevated abundance of Fe 3ϩ is a consequence of crystallographic constraints imposed by high-pressure host phases. Upon decompression and stabilization of upper-mantle minerals with abundant Fe 2ϩ sites, the Fe 3ϩ and Fe 0 react in the reverse direction of the Fe 2ϩ disproportionation proposed by (21) 2Fe 3ϩ ϩ Fe 0 3 3Fe 2ϩ , and, if all Fe 0 is consumed, the fO 2 rises to the observed values of the upper mantle. In the present case, this reaction took place outside of chromite but the low fO 2 was preserved within massive chromite because of the abundant reduced phases within a highly restricted, refractory, chemical environment.…”
Section: Terrestrial Nitrides and Single Crystals Tio2 II As Inclusiomentioning
confidence: 99%
See 1 more Smart Citation
“…Given the totality of these observations, we suggest that the resolution of conflicting fO 2 indicators is that in the deep mantle (Ͼ300 km) the fO 2 is low and the elevated abundance of Fe 3ϩ is a consequence of crystallographic constraints imposed by high-pressure host phases. Upon decompression and stabilization of upper-mantle minerals with abundant Fe 2ϩ sites, the Fe 3ϩ and Fe 0 react in the reverse direction of the Fe 2ϩ disproportionation proposed by (21) 2Fe 3ϩ ϩ Fe 0 3 3Fe 2ϩ , and, if all Fe 0 is consumed, the fO 2 rises to the observed values of the upper mantle. In the present case, this reaction took place outside of chromite but the low fO 2 was preserved within massive chromite because of the abundant reduced phases within a highly restricted, refractory, chemical environment.…”
Section: Terrestrial Nitrides and Single Crystals Tio2 II As Inclusiomentioning
confidence: 99%
“…Another perplexing aspect of this problem is the very low fO 2 conditions of these materials, including SiC (12), although the latter is not incorporated in this particular specimen. Recent experimental work has shown that, under conditions of the lower mantle (21,22) and even deep upper mantle (23), ferrous ion disproportionates into ferric ion ϩ Fe metal. Thus, it may be that only the outermost shell of Earth [perhaps as thin as Ϸ250 km (23)] is strongly oxidized and that it should be expected that rocks/ minerals brought to shallow levels from great depth could arrive highly reduced if protected during their last few hundred kilometers of travel.…”
Section: Terrestrial Nitrides and Single Crystals Tio2 II As Inclusiomentioning
confidence: 99%
“…Depending on speciation, this mechanism may also explain why some moderately volatile elements, like K, do not appear to show strong isotopic fractionation between terrestrial and lunar materials. Oxidation of the Earth's mantle could have been triggered by sequestration of the impactor's core into the terrestrial core, or through the sudden increase in size of the Earth from accretion of the Moon-forming impactor, increasing generation of Mg-rich perovskite at the base of a terrestrial magma ocean, forcing disproportionation of ferrous iron into ferric iron plus metal [88,89]. On the other hand, new high-pressure elemental partitioning experiments have shown that the Earth's core could have been formed under rather oxidizing conditions [62].…”
Section: (B) Volatile Loss During the Earth-moon Forming Giant Impact?mentioning
confidence: 99%
“…Integral to most 'homogeneous' accretion models is the concept that changes in metal-silicate partition coefficients at high pressures and temperatures may negate the necessity for changing f O 2 during core formation (Li & Agee 1996;Chabot & Agee 2003;Wade & Wood 2005). In addition, however, several fractionation processes involving Fe, O and Si have been identified, which could have changed the oxidation state of the mantle, even if the redox state of accreting material remained essentially constant (Javoy 1995;Frost et al 2004;Rubie et al 2004;Galimov 2005). It is, therefore, important to determine the effectiveness of these processes and the conditions under which they may have operated.…”
Section: Introductionmentioning
confidence: 99%